2022
DOI: 10.1108/pr-08-2019-0427
|View full text |Cite
|
Sign up to set email alerts
|

Retention and turnover of staff undertaking degree studies: insights and evidence from South Africa

Abstract: PurposeSocial exchange theory predicts that perceptions of employee/employer exchange relationships may change as employees add educational qualifications. Literature also suggests that more innovative individuals, who are particularly important to organisations, may be more likely to change jobs. The purpose of this study is to test how the innovativeness of an individual differs in its contribution to retention when subjected to different mediating and moderating influences indicated in the literature, for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 84 publications
0
0
0
Order By: Relevance
“…The difficulty in the South African public sector is that the government has standardised packages and benefits, whereas the private sector has the capacity to surpass and even outbid offers for scarce skills (Fernandez & Madumo, 2023). The findings of Adriano & Callaghan's (2022) study demonstrated that highly innovative individuals are often highly valued in the workplace, given the competitive constraints that organisations experience. These individuals appear to have much higher turnover intentions and may be more difficult to keep.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The difficulty in the South African public sector is that the government has standardised packages and benefits, whereas the private sector has the capacity to surpass and even outbid offers for scarce skills (Fernandez & Madumo, 2023). The findings of Adriano & Callaghan's (2022) study demonstrated that highly innovative individuals are often highly valued in the workplace, given the competitive constraints that organisations experience. These individuals appear to have much higher turnover intentions and may be more difficult to keep.…”
Section: Introductionmentioning
confidence: 94%
“…Employee turnover is expensive. Total turnover costs, for example, have been found to range from a minimum of one to a maximum of two years' salary and benefits for an individual employee (Adriano & Callaghan, 2022). Turnover is undoubtedly negatively associated with performance for the fundamental aim of the organisation (Meier & Hicklin, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It is argued that employees with a greater level of job satisfaction are more likely to transfer the learned knowledge and skills into their workplace and improve their performance compared to the less satisfied trainees (Islam & Ahmed, 2019;Wahyono et al, 2021). Thus, at the organisational level, satisfied employees essentially contribute to the effectiveness of the organisation and the ultimate long-term success, while dissatisfied employees provide little help for organisational success (Adriano & Callaghan, 2022;Wahyono et al, 2021).…”
Section: Identification Of Leadership Development Interventions Leade...mentioning
confidence: 99%